Comparative Transcriptomic Analysis of Root Cadmium Responses in Two Chinese Rice Cultivars Yuzhenxiang and Xiangwanxian 12 - Shangdu Zhang; Zhenliang Luo; Xiang Wu; Bangzhi Shi; Huidan Jiang; Leliang Zhou; Lianyang Bai (Journal of Chemistry)
Cadmium (Cd) pollution in paddy soil is an increasingly serious issue in rice production. It has been reported that there is a higher or lower grain Cd accumulation in the rice cultivars Yuzhenxiang (YZX) or Xiangwanxian 12 (XWX), respectively. To better manage the Cd pollution problem, the genes that might play vital roles in governing the difference in root Cd responses between these two rice cultivars were examined. In this study, the results of RNA sequencing (RNA-seq) showed that there were 341 and 161 differentially expressed genes in the roots of YZX and XWX after Cd exposure, respectively. Among these genes, 7 genes, such as Os06g0196300 (OsJ_019618), Os07g0570700 (OsJ_24808), ADI1, GDCSH, HSFB2C, PEX11-4, and CLPB1, possessed higher degree nodes with each other, through interaction analysis by the STRING (search tool for the retrieval of interacting genes/proteins) software, suggesting that they might play vital roles in Cd response. Based on GO enrichment analysis, 41 differently expressed genes after Cd treatment in YZX or XWX were identified to be related to Cd response. Through comparative transcriptomic analysis, 257 genes might be associated with the root Cd response difference between YZX and XWX. Furthermore, we supposed that ADI1, CFBP1, PEX11-4, OsJ_019618, OsJ_24808, GDCSH, CLPB1, LAC6, and WNK3 might be implicated in Cd response based on the combined analysis of RT-qPCR, interaction, and GO annotation analysis. In conclusion, the numerous genes that might be related to Cd stress response and root Cd response difference between YZX and XWX at the booting stage may be of benefit for the development of rice varieties with low Cd consumption.